Add MS 23121 (AM Scholar: Medieval and Early Modern Studies., 2019)
Description: Contents include: f.2. The Earl of Middleton to Charles II, London, January 5, 1664. His resignation of "the offices of Captain generall of your Majestie's kingdome of Scotland, and of captain and keeper of your Majestie's Castle of Edinburgh..." Rothes succeeds Middleton in these offices; a triumph for Lauderdale. Middleton later became Governor of Tangiers.; f.6. The Earl of Rothes to the Earl of Lauderdale, January the 7, 1664.; f.29. Lord Balcarres to the Earl of Lauderdale, Balcarres, January 23, 1664.; f.53. Lord Belllenden to the Earl of Lauderdale, Edinburgh, 20 February, 1664.